Pengaruh Likuiditas, Solvabilitas, dan Aktivitas terhadap Profitabilitas Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2022–2023 - Soleha, Soleha; Aminah, Aminah (Jurnal EMT KITA, 2026)
This study aims to evaluate the disclosure of the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2023 period. Using a descriptive quantitative approach, data was obtained from the annual financial statements of 28 companies using the purposive sampling method. The results showed that solvency had a significant negative effect on financial performance, while liquidity and activity had no significant effect. The study highlights the importance of transparency in the disclosure of financial statements in accordance with applicable standards and adds company size as a control variable for a more comprehensive analysis. These findings provide valuable insights for investors and company management in making investment decisions and improving financial strategies. With this update and increase in transparency, it is hoped that the company's financial performance can be better and can increase investor confidence in the mining sector. This research is expected to increase accountability and transparency of financial information in the mining sector.